A model for Enhancing Academic Staff Promotion System in Vocational and Technical Education: College of Technological Studies, As A Case Kuwait - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
Vocational and technical colleges and schools is a type of education which place students on apprenticeship system. It is through which students can spend certain time in industry premises to gain the necessary skills and attitudes mostly required by industries. Vocational and technical education is completely different from a formal education that is taught in classrooms. Developing countries (e.g., Kuwait, Oman, Qatar), has realized the importance of vocational and technical education in vital sectors of the economy (e.g., oil, electricity and water, construction), where expatriates are the dominate workforce and the need to reduce dependence on expatriates is one of high governments manpower strategy. In Kuwait, the government has absorbed the need to reduce dependence on expatriates and thus established the College of Technological Studies, CTS, to respond to the urgent need of skilled and semi-skilled indigenous workforce. Thus, the management of the College of Technological Studies has to apricate and value the significant role of the College of Technological Studies in meeting government workforce objectives. This can be accomplished by ensuring that academic staff has the necessary skills to prepare students to meet industrial needs and ambitious. The academic staff promotion system must be one of the CTS management priorities. The constant review and update the academic staff promotion system is crucial to maintain high standard of vocational and technical graduates. A model is introduced in this research for academic staff promotion system that enable the CTS management to review and assess the quality of the CTS academic staff competencies and their ability in meeting industrial requirements. The new model for academic staff promotion system would overcome and/or reduce the deficiencies of the current academic staff promotion system. The new model would encompass more realistic and efficient criteria’s for assessing the performance of vocational and technical academic staff and introduce a proper work methodology and procedure for minimizing the percentage of errors while promoting a candidate to a higher academic status.